Subject and Scripture: Exploring Existential Moments in the Ordinary Reading of Scripture - Hambali, R. Yuli Ahmad (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2023)
Scripture reading is not only a means of extracting meaning from sacred texts, but also a way to attain certain spiritual experiences. In the Islamic tradition, reading the scriptural text, such as the holy Quran, can lead readers to certain spiritual experiences that may fundamentally alter their awareness and understanding of reality. These experiences are accessible not only to readers with certain modalities but also to ordinary readers. This study analyses how ordinary readers can experience these existential moments. Data was collected through a literature review and documentation of the experiences of ordinary readers who have had spiritual-existential moments while reading scripture (the holy Quran). Data was analysed using Heidegger’s phenomenological hermeneutics. The results of the study indicate that readers of scripture, such as the holy Quran, have the same potential to experience existential moments that can alter their awareness and perspective on the meaning of life. These existential moments are moments of revelation of the meaning and divine guidance within oneself, allowing the reader to gain spiritual experience. The nature of scripture and the role of God as the author who is continuously present throughout the reading process allows even ordinary readers to experience existential moments that can alter their awareness and their way of being in the world.